Analysis (LibQual) on Loyalty and Library Satisfaction; A Case Study in YARSI University Library Service Center - Rizky, Tiko Dhafin; Huda, Nurul; Muslikh, Muslikh; Rini, Nova (LPPM Universitas Terbuka, 2020)
This study aims to analyze (LibQual): the effect of the performance of officers (affect of service) on user satisfaction; the effect of information access on user satisfaction; the influence of instructions and means of access (personal control) to the satisfaction of users; the effect of facilities and infrastructure (library as a place) on user satisfaction; the effect of the satisfaction of the visitors on the user loyalty; the effect (LibQual) on the loyalty of the visitors; the effect (LibQual) on the loyalty of the visitors through the variable user satisfaction. The data analysis method uses Structural Equation Model (SEM) with Lisrel 8.8 software. Respondents in this study were 180 students from YARSI University. This study presents a relative risk as a measure of effect size for categorical outcomes. Findings. The results of this study indicate that the LibQual component has a positive and significant influence on the visitors’ satisfaction and loyalty directly. Library satisfaction has a positive and significant effect on the loyalty of users directly. The LibQual component has a positive and significant indirect effect on loyalty through user satisfaction.